2013
DOI: 10.4314/ajtcam.v11i1.22
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the anti-diarrhea function of compound Chinese herbal medicine cangpo oral liquid

Abstract: Background: Diarrhea is a big problem in piglets. Cangpo Oral Liquid (COL) is a compound of Chinese herbal medicine. The preparation was fed to piglets had diarrheal disease in order to determine its anti-diarrhea activity and potential applications in vivo. Materials and Methods:The contents of Berberine hydrochloride, Magnolol and Honokiol in COL were performed on HPLC analysis. Organ bath was used to investigate the effect of COL on peristaltic reflexes and peristaltic waves in vitro. And anti-diarrhea acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Berberine hydrochloride in Cangpo oral liquid was determined to be 970 μg/mL by using TLC coupled with HPLC to evaluate the therapeutic potentials for anti‐diarrhea property. . Benzene/ethyl acetate/methanol/isopropyl alcohol/strong ammonia solution (12:6:3:3:1, v/v) was used as the developing solvent and finally observing it under the UV at 365 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Berberine hydrochloride in Cangpo oral liquid was determined to be 970 μg/mL by using TLC coupled with HPLC to evaluate the therapeutic potentials for anti‐diarrhea property. . Benzene/ethyl acetate/methanol/isopropyl alcohol/strong ammonia solution (12:6:3:3:1, v/v) was used as the developing solvent and finally observing it under the UV at 365 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Magnolol is a 4-allyl-2-(5-allyl-2-hydroxy-phenyl) phenol, and is present in considerable quantities in the bark of the Houpu magnolia ( Magnolia officinalis ) ( Lin et al., 2016a ). Previous data revealed that magnolol had anti-inflammatory ( Wang et al., 2015 ), antineoplastic ( Wu et al., 2014 ), anti-stress ( Chang et al., 2003 ) and antidiarrheic effects ( Guerra-Araiza et al., 2013 , Xia et al., 2013 ). Especially, a strong antioxidant effect has been observed both in in vitro and in vivo assays for magnolol ( Shen et al., 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Berberine (BBR) is a compound derived from the traditional Chinese medicine plants and has dramatically therapeutic potential against inflammation, diarrhea and so on. 16,17 Clinical evidence suggested that BBR was a fantastic cholesterol-lowering drug with its unique mechanism different from statins. 18 A large body of experimental data has supported the notion that BBR preconditioning attenuates I/R injury of various organs including kidney, heart, and intestine.…”
Section: Introductionmentioning
confidence: 99%